Aortic arch repair with extended end-to-side anastomosis in neonates and infants with transverse arch hypoplasia: Aortic arch repair in neonates and infants - Doyurgan, Onur; Balık, Hasan (Journal of Surgery and Medicine, 2023)
Background/Aim: The use of patches to repair the aortic arch is believed to have a positive effect on long-term morbidity. In this study, perioperative and follow-up data of patients who underwent transverse arch repair with a patch were compared with the data of patients who underwent end-to-end anastomosis (ESA). Methods: In this retrospective cohort study, the data of 27 patients (including 18 newborns) who underwent aortic arch repair at the Gazi Yasargil Education and Research Hospital between January 2018 and April 2023 were analyzed. The inclusion criteria included a diagnosis of proximal and distal transverse aortic arch hypoplasia, an age younger than 12 months of age, and the completion of aortic arch repair using cardiopulmonary bypass. Patients who underwent recoarctation repair due to residual obstruction, patients with single ventricular physiology, and patients who underwent aortic arch repair via a lateral thoracotomy without undergoing cardiopulmonary bypass were excluded from the study. The patients were divided into two groups. Group 1 included individuals who underwent aortic anterior wall expansion with autologous pericardium in addition to ESA; Group 2 included patients who underwent ESA only. Results: The median age of the patients was 21 days (range: 6–365 days), and the median body weight of the cohort was 3.5 kilograms (range: 2.4–8.9 kilograms). Enlargement with autologous pericardial patch was applied to 11 patients (40.7%). Surgical procedures performed in addition to arch repair included eight ventricular septal defect closures, six instances of pulmonary banding, three atrial septal defect closures, and one subvalvular pulmonary stenosis repair. The in-hospital mortality rate was 11.1% (n=3). Those three patients died due to sepsis. The median follow-up period was 152 days (range: 10–1316 days). Recoarctation requiring re-intervention did not occur in any of the studied patients. The antegrade selective cerebral perfusion time was statistically significantly longer in patients who underwent aortic arch repair using a patch (P=0.03). Conclusion: Repair of the arch with a patch may contribute to a reduction in long-term mortality and morbidity. However, there is a need for more comprehensive and long-term follow-up studies to verify these findings.